Study and Analysis of SEMG Signal between Elbow and Shoulder using Labview - Aggarwal, Ashish (My University, 2011)
Prosthesis is an artificial extension that replaces a missing body part. Prostheses are typically used to replace parts lost by injury or missing from birth or to supplement defective body parts. In addition to the standard artificial limb for every-day use, many amputees have special limbs and devices to aid in the participation of sports and recreational activities. Prosthetic arm is a boon for those persons who have lost their arm (below elbow) due some mishap. One of the main requirements of artificial arm is that functionally, it should be as near to the natural hand as possible. Various designs of artificial arm are available in the market, categorized as mechanical, electrical and Myo-electric arm. Mechanical devices are functional prostheses that use some motion of the body to provide the force necessary to control the prosthetic component. Electrical arms operate the hand by a motor driven by micro switches and relays. Myo-Electric arm is stimulated by muscle signal available from the stump of amputee. In the present research work, SEMG signals were taken by active electrodes between elbow and shoulder with different forces. Signal is acquired in soft scope Labview by DAQ card (NI DAQ 6024E). The SEMG signal at different positions above elbow for various movements like up (m1)/down (m2), clockwise (m3)/anticlockwise (m4) of arm was carried out. After acquiring data from different locations above elbow with different forces, analysis were made using RMS values, standard deviation, power spectrum, time frequency distributions (WVD, CWD).
M.E. (Electronic Instrumentation and Control)
Keywords: SEMG Signal; Labview